2014
DOI: 10.1039/c3ob42414f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a carborane-containing cholesterol derivative and evaluation as a potential dual agent for MRI/BNCT applications

Abstract: Abstract.In this study the synthesis and characterization of a new dual, imaging and therapeutic, agent is proposed with the aim of improving the efficacy of Boron Neutron Capture Therapy (BNCT) in cancer treatment. The agent (Gd-B-AC01) consists of a carborane unit (ten boron atoms) bearing a cholesterol unit on one side (to pursue the incorporation into the liposome bi-layer), and a Gd(III)/1,4,7,10-tetraazacyclododecane monoamide complex on the other side (as MRI reporter to attain the quantification of B/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Propargylamine (3.0 g, 54.5 mmol) was dissolved in 100 mL of dichloromethane (DCM) and 100 mL of saturated aqueous sodium bicarbonate (NaHCO 3 ) were added. HRMS (m/z): Calcd for C 19 The reaction mixture was slowly allowed to warm to room temperature (RT).…”
Section: General Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Propargylamine (3.0 g, 54.5 mmol) was dissolved in 100 mL of dichloromethane (DCM) and 100 mL of saturated aqueous sodium bicarbonate (NaHCO 3 ) were added. HRMS (m/z): Calcd for C 19 The reaction mixture was slowly allowed to warm to room temperature (RT).…”
Section: General Informationmentioning
confidence: 99%
“…15 However, later it was found that this compound was not suitable for BNCT due to poor tumor accumulation. [17][18][19] Results and discussion Synthesis of CB-GdDOTA-MA Our efforts to prepare CB-GdDOTA-MA started with the synthesis of alkyne 1 in 89% yield by reacting propargylamine with bromoacetyl bromide. Such lipophilic conjugates are designed to form nanoparticles (micelles or liposomes) and deliver sufficient boron atoms to the tumor via the enhanced permeability and retention (EPR) effect.…”
Section: Introductionmentioning
confidence: 99%
“…Dicarba-closo-dodecaboranes are attractive synthons for developing inorganic pharmaceuticals [1][2][3][4][5][6][7][8], radiopharmaceuticals [9], fluorophores [10], and boron neutron capture therapy (BNCT) [11][12][13][14][15] or synovectomy (BNCS) agents [16,17]. Carboranes are biocompatible, resistant to enzymatic modification, and can be linked to or incorporated within a variety of different targeting vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The LET range is limited to a diameter of 5-9 ÎŒm which is in accord with the size of a single cell. [11][12][13][14] However, carborane compounds are generally hydrophobic substances which cannot be dispersed in aqueous solution. A higher total dose can be received than that of the adjacent normal tissues resulting from a greater concentration of 10 B in tumor cells.…”
Section: Introductionmentioning
confidence: 99%